7. A COMPARATIVE ANALYSIS OF SPUKTA REGULATIONS: A STUDY OF VLOS OPERATIONAL PROCEDURES IN CONTROLLED AIRSPACE BETWEEN THE FAA, EASA, AND DGCA INDONESIA - Muchammad Furqon; Ahmad Ilham; Ferdy Susanto; Kamal Muchdatas; Suroso; Salsabila (Jurnal TNI Angkatan Udara, 2026)
This study aims to critically analyze and compare the SPUKTA VLOS operationalprocedure framework in the Control Area established by three major aviation authorities: theFederal Aviation Administration (FAA), the European Union Aviation Safety Agency (EASA),and the Directorate General of Civil Aviation (DGCA) Indonesia. The integration of SmallUnmanned Aircraft Systems (SPUKTA) or drones into civil airspace, particularly in the ControlArea (CTR), requires strict and uniform operational procedures. The most common Visual Lineof Sight (VLOS) operations pose a high risk in controlled airspace if not properly regulated.Using a descriptive qualitative method with comparative content analysis of primary regulatorydocuments (FAA Part 107, EASA Reg. (EU) 2019/947, pm 37 of 2020 and PM 63 of2021/CASR Part 107 Indonesia), the comparison focuses on five key procedural variables:Operational Clearance Mechanism, Operational Altitude Limit, Pilot CommunicationRequirements, Time Window Provisions, and Pre-flight Procedures. The results show thatwhile the FAA and EASA offer mature systems (automated LAANC vs. risk-based Geozone),the Indonesian DGCA relies on manual permitting processes and local authority discretion.This disparity indicates a gap in regional automation and standardization. This studyrecommends that the Indonesian DGCA consider implementing a real-time authorizationsystem and digital Geozone to improve compliance and efficiency of VLOS SPUKTAoperations in the Control Area.